2022
DOI: 10.3390/foods11020182
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Curcumin Hydrogel Beads for the Development of Functional Kulfi: A Tailoring Delivery System

Abstract: Curcumin has been demonstrated to have biological activities and its fortification in food products is an important strategy to deliver bioactive ingredients at target sites. However, studies have documented a curcumin low bioavailability and low intake. Hence, combining functional ingredients with food should be needed to prevent widespread nutrient intake shortfalls and associated deficiencies. Thus, curcumin was encapsulated in calcium-alginate and their characteristics as well as in vitro release behavior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…There are also studies available on the use of nanoemulsions of natural functional ingredients to support the development of probiotic cultures and secure the recommended level of 6 log CFU/g during the entire storage period ( 52 ). Sharma et al ( 53 ) confirmed the ability of curcumin to significantly reduce the growth of yeast and mold in functional dairy, which was observed in this experiment. The more pronounced antimicrobial effect of N than for TE is a consequence of its specific formulation enabling the release of curcumin on the surface of the bacterial cell and into its membrane, which enables it to exhibit an inhibitory effect with the formation of a bacterial biofilm ( 45 , 54 ).…”
Section: Discussionsupporting
confidence: 81%
“…There are also studies available on the use of nanoemulsions of natural functional ingredients to support the development of probiotic cultures and secure the recommended level of 6 log CFU/g during the entire storage period ( 52 ). Sharma et al ( 53 ) confirmed the ability of curcumin to significantly reduce the growth of yeast and mold in functional dairy, which was observed in this experiment. The more pronounced antimicrobial effect of N than for TE is a consequence of its specific formulation enabling the release of curcumin on the surface of the bacterial cell and into its membrane, which enables it to exhibit an inhibitory effect with the formation of a bacterial biofilm ( 45 , 54 ).…”
Section: Discussionsupporting
confidence: 81%
“…Mobaraki et al, [64] Hydrogel bead Ionotropic gelation method Curcumin 2% GIT Controlled drug release is achieved with this formulation under simulated GI conditions. Sharma et al, [65] Nanoparticle -Curcumin 1% w/v Intestine (Colon)…”
Section: Sharma Et Al [60]mentioning
confidence: 99%
“…The FTIR spectra of CUR, INIC, and CUR-INIC are shown in Figure 3. The CUR spectra showed an absorption peak at 3500 cm −1 , indicating stretching vibrations of O-H phenolic, 1626 cm −1 associated with stretching vibrations of C=C and C=O, 1601 cm −1 associated with C=C stretching vibrations of the aromatic ring, 1505 cm −1 associated with vibrations of C=O, 1262 cm −1 associated with vibrations of aromatic C-O (enol groups), and 1026 cm −1 associated with vibrations of C-O-C group (Sharma et al, 2022) . INIC has a spectrum with absorption peaks at 3363 and 3177 cm −1 , showing stretching vibrations of asymmetric and asymmetric N-H, 1657 cm −1 associated with stretching vibrations of C=O amide, 1621 cm −1 associated with bending vibrations of amide N-H, and 1408 cm −1 is related to the stretching vibrations of C-N amide (Ferreira et al, 2022) .…”
Section: Ftir Spectramentioning
confidence: 99%